The influence of entrepreneurial orientation and market orientation on SME business performance - Dini Abshar; Whyosi Septrizola (Universitas Negeri Padang, 2023)
This study aims to examine the impact of entrepreneurial orientation and market orientation on the business performance of small and medium-sized enterprises (SMEs) in Padang. The population of this study consists solely of Padang-based SMBs. While the number of samples in this study was 97 individuals, 100 samples of SMEs in Padang City were collected. Using a standardized questionnaire, respondents will be asked to rate their entrepreneurial orientation and market orientation in an effort to enhance the success of the firm they are now operating. The data were then analysed using SPSS version 21 and multiple regression analysis. (1) Entrepreneurial orientation has a significant positive influence on business performance variables, and (2) Market orientation has a strong positive influence on company performance variables.